An Unhappy Happy Port: Fin-de-siècle Port Said and Its Connections and Disconnections of Water and Iron. (November 2022) - Carminati, Lucia
Abstract : A joke appearing in the folds of a Cairo-based newspaper published in Italian in 1895 must have fallen flat with Port Said's inhabitants. But the irony was not amiss. The jest suggested that the town, whose toponym could be translated to "happy port" given the Arabic meaning of saʿīd, ought to be renamed "unhappy" due to the sad state of its public services. Readers may have smiled mirthlessly in agreement with the author, who claimed the Egyptian government treated the city "as if it were less than a village." Many were under the impression that Cairo wanted to scrap this "unhappy happy port" from the rest of Egypt. Continuing the wordplay, British journalist George Warrington Steevens wrote in 1898 that Port Said "would be wonderful if it were not unhappy, " stuck as it was between its riotous past and its doubtfully industrious future. Puns based on Port Said's name must have circulated for a while. Already in 1875, a French author had ironically remarked that this town's auspicious name seemed quite unjustified.